2022
DOI: 10.31222/osf.io/gaj43
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why don’t we share data and code? Perceived barriers and benefits to public archiving practices

Abstract: The biological sciences community is increasingly recognizing the value of open, reproducible, and transparent research practices for science and society at large. Despite this recognition, many researchers remain reluctant to share their data and code publicly. This hesitation may arise from knowledge barriers about how to archive data and code, concerns about its re-use, and misaligned career incentives. Here, we define, categorise, and discuss barriers to data and code sharing that are relevant to many rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Evolving methods, the availability and support for large scale data sharing have led to increased attention and resources to enable scientists to share data (Tenopir et al, 2011). Despite computational and storage infrastructure being in place, there are still perceived barriers to effective data sharing (Tenopir et al, 2011) and code sharing (Gomes et al, 2022). In a survey of >1300 scientists on data sharing practices, Tenopir et al, (2011) found that one third of the respondents chose not to answer whether they make their data available to others, and of those that did respond 46% reported they do not make their data electronically available to others.…”
Section: Reproducibility Repeatability and Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Evolving methods, the availability and support for large scale data sharing have led to increased attention and resources to enable scientists to share data (Tenopir et al, 2011). Despite computational and storage infrastructure being in place, there are still perceived barriers to effective data sharing (Tenopir et al, 2011) and code sharing (Gomes et al, 2022). In a survey of >1300 scientists on data sharing practices, Tenopir et al, (2011) found that one third of the respondents chose not to answer whether they make their data available to others, and of those that did respond 46% reported they do not make their data electronically available to others.…”
Section: Reproducibility Repeatability and Data Availabilitymentioning
confidence: 99%
“…In exploring why researchers chose not to make their data available Tenopir et al, (2011) found the leading reason is insufficient time (54%), followed by lack of funding (40%), having no place to put the data (24%), lack of standards (20%), and "sponsor does not require" (17%), with only 14% of respondents stating their data "Should not be available". For code sharing, Gomes et al, (2022) identified reasons why code sharing is not more common in biological sciences, including perceived barriers such as: unclear process, complex workflows, data too large, lack of incentives, and concerns on re-use of data.…”
Section: Reproducibility Repeatability and Data Availabilitymentioning
confidence: 99%
“…A third barrier may come from general reluctance to share data and code publicly, or technical and logistical issues 16 . GitHub is, by default, a public and open platform.…”
Section: Why Aren't More Eeb Researchers Using Github?mentioning
confidence: 99%
“…Widespread adoption of GitHub for collaborating on research tasks can ultimately enable EEB researchers to spend less time on creating novel processes for collaboration and more time on their research 14 . More importantly, expanding the availability of data and code management standards -of which GitHub is one increasingly important component -makes research more reproducible and collaborative 15,16 . This paper is the result of an academic hackathon held during the 2021 conference for the Society for Open, Reliable, and Transparent Ecology and Evolutionary Biology (SORTEE, https://www.sortee.org).…”
Section: Introductionmentioning
confidence: 99%
“…However, while this may be advantageous for researchers, it goes against the progress of science and conservation. Besides, authors should not see data as their property, because typically, data collection has been funded with public money, so publications should not only produce results but also the data generated to foster new research (Gomes et al, 2022).…”
Section: Impac T Of Tr An S Iti On To Open Acce Ssmentioning
confidence: 99%